2018
DOI: 10.3390/foods7090142
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential of Grass Pea Seeds from European Countries

Abstract: Phenolic compounds were extracted from seeds of 30 varieties of grass pea (Lathyrus sativus) into 80% (v/v) methanol. The total phenolics compounds content of the extracts and their antioxidant activity were determined using Folin-Ciocalteu’s phenol reagent and 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and ferric-reducing antioxidant power (FRAP) methods, respectively. Total phenolic contents ranged from 1.88 to 7.12 mg/g extract and 20.3 to 70.3 mg/100 g seeds. The extracts and seeds were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 37 publications
2
12
1
2
Order By: Relevance
“…The results of ABTS assay obtained in this study for faba bean extracts were much higher than those reported before for extracts of grass pea (0.017-0.037 mmol Trolox/g) [32], cow pea (0.285-0.665 mmol Trolox/g) [43], white bean (0.0270-0.043 mmol Trolox/g) [29], mung bean (0.021-0.031 mmol Trolox/g) [35], and lupin (0.260-0.620 mmol Trolox/g) [31]. The results of FRAP assay were also much higher than those reported for extracts of grass pea (0.045-0.120 mmol Fe 2+ /g), [32], cow pea (0.487-1.566 mmol Fe 2+ /g) [43], white bean (0.066-0.089 mmol Fe 2+ /g) [29], and lupin 0.046-0.064 [31].…”
Section: Antioxidant Activitycontrasting
confidence: 83%
See 2 more Smart Citations
“…The results of ABTS assay obtained in this study for faba bean extracts were much higher than those reported before for extracts of grass pea (0.017-0.037 mmol Trolox/g) [32], cow pea (0.285-0.665 mmol Trolox/g) [43], white bean (0.0270-0.043 mmol Trolox/g) [29], mung bean (0.021-0.031 mmol Trolox/g) [35], and lupin (0.260-0.620 mmol Trolox/g) [31]. The results of FRAP assay were also much higher than those reported for extracts of grass pea (0.045-0.120 mmol Fe 2+ /g), [32], cow pea (0.487-1.566 mmol Fe 2+ /g) [43], white bean (0.066-0.089 mmol Fe 2+ /g) [29], and lupin 0.046-0.064 [31].…”
Section: Antioxidant Activitycontrasting
confidence: 83%
“…The results obtained in this research confirm the fact that faba bean is a rich source of phenolic compounds as well as condensed tannins. A lower content of total phenolic compounds was previously reported for extracts of pea [28], white bean [29], broad bean [23,30] lupin [31], and grass pea [32]. A similarly high content of total phenolic compounds was previously reported for red lentil [33], green lentil [34], red bean [35], and adzuki bean [36].…”
Section: Content Of Total Phenolics and Condensed Tanninssupporting
confidence: 62%
See 1 more Smart Citation
“…Fratianni et al (2014) reported similar content of total phenolics in two Italian varieties of grass pea (20.6 and 21.3 mg/100 g). In the study of Wang et al (1998), the content of total phenolics in Canadian grass pea ranged from 16.2 to 37.5 mg/100 g. Seeds of Spanish, Italian, French, Polish, and German lines of Lthyrus sativus were characterized by the content of total phenolics that ranged from 20.3 to 70.3 mg/100 g (Rybiński et al, 2018). However, the higher contents of total phenolic compounds in grass pea were reported by Carbonaro et al (2015) and Wiszniewska and Piwowarczyk (2015).…”
Section: Content Of Total Phenolicsmentioning
confidence: 99%
“…An interesting example is grass pea ( Lathyrus sativus L.) seeds, which contain valuable proteins and a relatively high level of mineral compounds. Grass pea seeds from European countries are considered a good source of phenols in a vegetarian diet, with dominant p -coumaric acid derivatives in the phenolic profile [ 2 ]. Moreover, fermentation of grass pea seeds with Rhizopus strains was proven to significantly enhance the total phenol level and antioxidant potential of the substrate [ 3 ].…”
Section: Introductionmentioning
confidence: 99%